Detection of SYT±SSX1/2 fusion transcripts by reverse transcriptase-polymerase chain reaction (RT-PCR) is a valuable diagnostic tool in synovial sarcoma - Willeke, Frank; Mechtersheimer, Gunhild; Schwarzbach, Matthias; Weitz, Jürgen; Zimmer, D.; Lehnert, Thomas; Herfarth, Christian; Knebel Doeberitz, Magnus von; Ridder, Rüdiger (European journal of cancer, 1998)
Cytogenetically, most synovial sarcomas are characterised by a specific chromosomal translocation [(X;18)(p11.2;q11.2)], which results in the generation of fusion transcripts comprising SYT (18q11) and either SSX1 or SSX2 (Xp11) sequences. By using a sensitive reverse transcriptase-polymerase chain reaction (RT-PCR) protocol, specific SYT-SSX1/2 fusion transcripts were detected in 10 histopathologically confirmed synovial sarcomas. Control tumours with morphological spindle cell patterns mimicking monophasic synovial sarcoma tested negative (18/19) in the RT-PCR protocol, with the exception of one spindle cell sarcoma originally classified as a fibrosarcoma. Furthermore, the established RT-PCR protocol was used to evaluate the feasibility of SYT-SSX1/2 fusion transcript detection for minimal residual disease analysis. Analyses of surgical margins revealed a fusion transcript in two of four operations for synovial sarcoma analysed, one of which was diagnosed with tumour free margins by conventional histopathology. These data suggest that the RT-PCR amplification of SYT-SSX1/2 fusion transcripts is a valuable tool in the differentiation of synovial sarcomas, especially in cases of equivocal morphology. Additionally, the RT-PCR approach may be used for the detection of residual tumour cells in synovial sarcoma patients.